The Effectiveness of Youtube Channel @Menjadi Human in Providing Understanding of Mental Health for Communications Students of UIN North Sumatera (International Journal of Cultural and Social Science, 2023)
Mental health is very important in human life because it is the main foundation that will determine how a person can accept and be accepted in his environment. This makes understanding mental health issues very important for every individual. In an effort to provide education on mental health issues, there is information about mental health that is packaged through narrative content on the YouTube channel "Being Human". This study aims to see how the effectiveness of the YouTube channel Being Human S is in providing an understanding of mental health issues for Communication Studies students at UIN North Sumatra. This study uses a qualitative approach with a type of field research (field research). The subjects in this study were 8 students of Communication Studies at UIN North Sumatra, taken using a purposive technique with predetermined criteria. The theory used is the theory of communication effectiveness by (Subagyo, 2010) which looks at communication effectiveness through six dimensions, namely the dimensions of the recipient, timeliness, message content, channel, message format and source. The results of the study show that the YouTube channel "Being Human" is effective in providing an understanding of mental health for Communication Studies students at UIN North Sumatra.